Library Service Management at the Bung Karno Library - Kalam, Muhammad Saiful; Putri, Gana Royanan (Prodi Ilmu Perpustakaan dan Informasi Universitas Islam Negeri Raden Fatah Palembang, 2025)
The National Library of the Republic of Indonesia (PNRI) is the largest library in Indonesia with a collection of more than 3.2 million items in 2024. Then, PNRI is an institution ranked 4th out of 584 state entities/institutions for public service compliance. This achievement is interesting to study and research how the management is carried out by PNRI. The location of this research was carried out at the Bung Karno Library UPT Blitar. This research uses a descriptive qualitative method. Data collection techniques through observation, interviews, and documentation. Based on the results of the research, management in the procurement of collections is carried out with purchases that are initially made by making desiderata, then delivering the card to the publisher. Purchases are made periodically every month, with trucks as a logistics medium. Processing is done by checking the suitability of the desiderata with the number of books received. Then provide 3 types of stamps, namely the date of receipt, no. parent on the ownership page on the three sections of the book. Next, fill in the no. DDC (Dewey Decimal Club) classification and put it on the shelf and input it into the shelf catalog data and computer. Finally, the service is carried out by inputting library and shelving data. The user fills out the book borrowing form and when finished reading, it is placed on the shelving shelf and inputted into the circulation data. In addition, the librarian reprimands via WhatsApp if the user is late in returning and is fined. Services outside the book include memorabilia services and in-out door guides. This study can be used as a reference for further research on library management in procurement, processing, and service.